Sure! Let's denote the three classmates as Classmate A, Classmate B, and Classmate C, and let’s assign them the following expressions:
- Classmate A: \( f(x) = 2x + 3 \)
- Classmate B: \( g(x) = x^2 - 5x + 6 \)
- Classmate C: \( h(x) = \frac{1}{x} + 2 \)
Each classmate substitutes \( x = 4 \) into their expression:
-
Classmate A: \[ f(4) = 2(4) + 3 = 8 + 3 = 11 \]
-
Classmate B: \[ g(4) = (4)^2 - 5(4) + 6 = 16 - 20 + 6 = 2 \]
-
Classmate C: \[ h(4) = \frac{1}{4} + 2 = 0.25 + 2 = 2.25 \]
To summarize, the results of their calculations are:
- Classmate A: \( 11 \)
- Classmate B: \( 2 \)
- Classmate C: \( 2.25 \)